Prevalence and types of bacterial infections of the upper respiratory tract at a tertiary care hospital in the City of Tripoli - Atia, Ahmed; Abired, Ahmed; Ammar, Anees; Elyounsi, Najla; Ashour, Abdulsalam (Libyan International Medical University Journal, 2018)
Aim: The study aimed to determine the bacterial etiology of upper tract respiratory infection in Abu-Sitta Hospital, Tripoli, Libya. Subjects and Methods: A total of 470 sputum specimens and 60 throat swabs were collected over a period of 1 year (From January 2014 to December 2014) from patients presented with clinical signs of upper respiratory tract infection at Abu-Sitta Hospital. Enrolled patients were sorted as inpatients or outpatients and by gender. Data were entered and analyzed using SPSS version 22.0. Variables were expressed as percentages. Differences in age and gender were analyzed using Chi-square test. Results: Of the total 530 screened samples, 80.5% were culture positive, where bacterial pathogens were detected in 83.7% of sputum specimens and in 56.5% of throat swabs. Streptococcus pneumoniae was the most prevalent (48%), followed by Pseudomonas aeruginosa (23%), Staphylococcus aureus (13%), Enterobacter (8%), Citrobacter freundil (5%), and latest with Klebsiella (3%). Conclusions: The spectrum of pathogenic bacterium causing upper respiratory infection in Abu-Sitta Hospital is considerably wide, with S. pneumoniae and P. aeruginosa being the major causative bacteria.
Keywords: Bacteria; respiratory infection; Tripoli